1995
DOI: 10.1136/bjo.79.9.814
|View full text |Cite
|
Sign up to set email alerts
|

Low vision in east African blind school students: need for optical low vision services.

Abstract: Aims-There is increasing awareness of the needs of children with low vision, particularly in developing countries where programmes of integrated education are being developed. However, appropriate low vision services are usually not available or affordable. The aims of this study were, firstly, to assess the need for spectacles and optical low vision devices in students with low vision in schools for the blind in Kenya and Uganda; secondly, to evaluate inexpensive locally produced low vision devices; and, fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
3
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 6 publications
4
54
3
3
Order By: Relevance
“…12,13 Sloan et al showed that children, compared to adults, have a very high rate of successful LVD use, when aids are properly prescribed. 14 The importance of the present study is highlighted by the fact, that LVD were not available in any of the schools, emphasizing the need to improve awareness of LVD among parents and teachers involved in educating the blind in the developing countries..…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Sloan et al showed that children, compared to adults, have a very high rate of successful LVD use, when aids are properly prescribed. 14 The importance of the present study is highlighted by the fact, that LVD were not available in any of the schools, emphasizing the need to improve awareness of LVD among parents and teachers involved in educating the blind in the developing countries..…”
Section: Discussionmentioning
confidence: 99%
“…Functional vision was assessed to determine if the child had useful residual vision for independent mobility (the ability to navigate without assistance between two chairs set 2 m apart in a well-lit room), social contact (the ability to recognize known faces at a distance of 2 m), and near vision (the ability to recognize or describe the shape of three 5 mm symbols at any near distance). 10 Assessment for refraction and low vision aids was performed in all children who were able to perform the tests for functional vision. Anterior segment examination was performed using a torch, magnifying loupe, and/or slit lamp.…”
Section: Methodsmentioning
confidence: 99%
“…For example, one blind school survey from Kenya and Uganda found that 36% of children would benefit from an optical low vision device. 25 Liaison between the tertiary centres and blind schools and mainstream schools with low vision units is essential as are studies to investigate the longer-term functional and educational status of these patients.…”
Section: (C) Visual Resultsmentioning
confidence: 99%